Testing the financial distress prediction model for sukuk-issuing companies in Malaysia - Mohamad Shafi, Roslina; Syed Mohd Zain, Sharifah Raihan; Mohid Rasid, Mohamed Eskandar Shah; Mydin Meera, Ahamed Kameel (Edward Elgar Publishing Limited, 2017)
Companies are exposed to business and financial risk and are affected by business cycles and economic downturns. A company is fortunate if it is capable of preventing and alleviating financial crises by utilizing existing financial distress models to deal with volatile markets and changes in the global economy. Such models are capable of signalling to a company worst case scenarios and remedial possibilities to prevent future distress. However, applying such risk models to sukuk-issuing companies remains a point of contention because sukuk and related bonds are fundamentally different types of financial instruments and possess dissimilar risk exposure to traditional instruments. The current study examines this difference by testing existing financial distress prediction models on sukuk-issuing companies. The results show that the Altman and Ohlson financial distress models were capable of alerting companies of possible financial distress with a 52.78 per cent prediction accuracy. Further testing revealed that the Ohlson model produced a higher prediction power than the Altman model for Malaysian sukuk-issuing companies. These signify that logit model is more powerful for sukuk issuing companies.